Echoes of the Mind: Between Subjective Experience and Scientific Understanding of Schizophrenia - Theiling, Justus (Satura, 2026)
This essay explores the complex interplay between the subjective experience of schizophrenia and its scientific understanding. It bridges the gap between literary portrayals of the disorder and the lived realities of patients by analyzing personal narratives. The author draws on qualitative data from interviews with individuals diagnosed with schizophrenia, some of whom attribute the onset of their illness to their engagement with literary and religious texts like Michael Ende’s Momo and the Mahabharata.